1996
DOI: 10.1046/j.1525-1438.1996.06010008.x
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factor analysis, for patients with no evidence of disease after initial chemotherapy for advanced epithelial ovarian carcinoma

Abstract: Although the results from chemotherapy for advanced ovarian carcinoma have improved over the past 15 years with the introduction of platinum compounds, there are still a large number of patients who will relapse from complete response (clinical or pathological) to first line therapy, and there is little published data on prognostic factors for survival after relapse. A total of 270 patients from two randomized trials in ovarian carcinoma conducted in Scotland were reviewed and the data from 117 patients who we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…In particular, ascites is gaining recognition as a unique form of tumor microenvironment responsible for hallmark of ovarian cancer. The link between the presence of ascites and ovarian cancer progression was first proposed by Lopez et al (5) Since then, numerous studies have contributed to the characterization of the ascites components, further revealing it's key roles in the hallmarks of ovarian cancer.To overcome the limitations of current anticancer agents, better understanding of EOC and its tumor microenvironment is needed. Remarkable progress has been made in research on malignant ascites, expanding our knowledge of both the cellular (tumor cells and stromal cells) and acellular (soluble factors) components (Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, ascites is gaining recognition as a unique form of tumor microenvironment responsible for hallmark of ovarian cancer. The link between the presence of ascites and ovarian cancer progression was first proposed by Lopez et al (5) Since then, numerous studies have contributed to the characterization of the ascites components, further revealing it's key roles in the hallmarks of ovarian cancer.To overcome the limitations of current anticancer agents, better understanding of EOC and its tumor microenvironment is needed. Remarkable progress has been made in research on malignant ascites, expanding our knowledge of both the cellular (tumor cells and stromal cells) and acellular (soluble factors) components (Fig.…”
mentioning
confidence: 99%
“…In particular, ascites is gaining recognition as a unique form of tumor microenvironment responsible for hallmark of ovarian cancer. The link between the presence of ascites and ovarian cancer progression was first proposed by Lopez et al . Since then, numerous studies have contributed to the characterization of the ascites components, further revealing it's key roles in the hallmarks of ovarian cancer.…”
mentioning
confidence: 99%
“…In these patients, treatment with surgery together with combination chemotherapy has resulted in a median progression-free survival of 16–22 months and a 5-year survival rate of 27% 5 , although better results are now being reported with improvements in therapy. One study has suggested that ascites at presentation is an independent prognostic factor for time to relapse 6 and, overall, more than one-third of women with ovarian cancer develop ascites during the course of their disease 3 , and this is not limited to any specific histological subtype. Although some oncologists consider that the incidence of ascites may be reducing with the widespread use of combination chemotherapy that incorporates taxanes, there are no published supporting data.…”
mentioning
confidence: 99%
“…delivery of the nanoformulation to delay the formation of ascites. More than one-third of women diagnosed with ovarian cancer will develop ascites from the disease (35, 36). Typically, treatment of the underlying disease will resolve the ascites but the development of chemoresistant disease results in intractable ascites.…”
Section: Discussionmentioning
confidence: 99%